PERAN MEDIASI KEPUASAN KERJA PADA HUBUNGAN MOTIVASI KERJA DENGAN INTENTION TO QUIT - Srinadi, Ni Nyoman; Supartha, Wayan Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 04.NO.03.TAHUN 2015, 2015)
The purpose of this study was to analyze the effect of work motivation on job satisfaction, motivation influence on intention to quit and influence job satisfaction with the intention to quit. Respondents in this study were all medical staff who served in Karangasem district health centers. In this study, all of population members are samples. Instruments research using questionnaires and analysis is PLS (Partial Least Square). The variables used are the work motivation, job satisfaction and intention to quit. The results of this study indicate that work motivation variable has a positive and significant effect on job satisfaction. Work motivation variable has a negative and significant effect on intention to quit. Job satisfaction variable has a negative and significant effect on intention to quit. To reduce the intention to quit is to increase motivation and job satisfaction. Intention to quit the decline is expected to improve the quality of care that can be given by medical staff. Its application can be done with a fair treatment from a health center head against medical staff, equal opportunities in terms of career promotion and fair distribution of services